THE CHALLENGES OF ISLAMIC CRIMINAL LAW IMPLEMENTATION IN ACEH SHARIAH COURT - Nasrullah, Nasrullah; Novendra, Carissa Shifa; Reyhan, M. Farel (Diponegoro Law Review, 2024)
This paper explores the reconstruction of Islamic criminal law within the Aceh Shariah Court, highlighting its historical, socio-cultural, and legal context. Aceh, recognized for its special autonomy and predominantly Muslim population, has enacted various qanuns (regional Islamic laws) since 2001 to implement Islamic Sharia, encompassing both civil and criminal law. The study employs non doctrinal research to analyze the framework and challenges of implementing Islamic criminal law in Aceh. The legal substance, including Law No. 11 of 2006 and various qanuns, facilitates public participation and supports the integration of Islamic principles into regional governance. The research discusses the pluralistic legal system in Aceh, incorporating state law, customary law, and Islamic law, and examines the role of the Sharia Court in adjudicating cases under Islamic law. The study identifies two main issues: the enforceability of the qanun concerning non-Muslims and human rights, and the proportionality of punishments. Despite criticisms, the qanuns aim to enhance justice and prosperity in Aceh, reflecting the strong religious and cultural identity of the region. The paper concludes by emphasizing the necessity of ongoing adaptation and refinement in the application of Islamic criminal law to address societal needs and uphold human rights.